Regional phase angle, not whole-body, is augmented in response to pre-season in professional soccer players - Honorato, R. D. C.; Ferraz, A. S. M.; Kassiano, W.; Martins, P. C.; Silva, D. A. S.; Ceccatto, V. M. (Research in Sports Medicine, 2023)
The objective of this article was to assess the effects of six-week pre-season training on whole-body and regional bioelectrical impedance analysis (BIA)-derived parameters, body composition, power, and aerobic performance in professional soccer players. Ten professional soccer athletes participated in the present study. Whole-body and regional hamstrings BIA-derived parameters [resistance, reactance, impedance, phase angle (PhA)], body composition, total body water (TBW), intracellular (ICW), and extracellular (ECW) were measured before, at mid-point, and after sixth week of the pre-season. Power (countermovement jump and squat jump) and aerobic capacity (Yo-Yo test) were measured before and after pre-season. There was a significant increase in the regional PhA (+13.9%) but not in the whole-body. There was a reduction in fat mass (-4.1%), an increase in fat-free mass (+1.7%), TBW (+8.3%), ICW (+8.8%), and ECW (+7.6%), as well as an increase in jump height (+11.0%) and distance covered in the Yo-Yo test (+34.7%). From our results, it is possible to suggest that pre-season training can induce an increase in hamstring PhA as well as body recomposition and improvement of physical fitness in professional soccer players.